2012
DOI: 10.1021/la304080c
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Poly(dopamine) Films Mixed with a Nonionic Polymer

Abstract: Poly(dopamine) (PDA) coatings have recently attracted considerable interest for a variety of applications. Here, we investigate the film deposition of dopamine mixed with a nonionic polymer (i.e., poly(ethylene glycol) (PEG), poly(vinyl alcohol) (PVA), and poly(N-vinyl pyrrolidone) (PVP)) onto silica substrates using X-ray photoelectron spectroscopy and quartz crystal microbalance. Furthermore, we assess the possibility of coating silica colloids to yield polymer capsules and liposomes with these mixtures. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 39 publications
7
118
0
Order By: Relevance
“…Zhang et al immersed substrates into the solution containing dopamine and non-ionic polymers for co-deposition coatings [133], and found that PEG and polyvinyl alcohol (PVA) are trapped in the PDA coating without any covalent bonding, while strong hydrogen-bond acceptor like poly(N-vinyl pyrrolidone) (PVP) would suppress the assembly of PDA and decrease the deposition amount of PDA. Taking advantage of the strong hydrogen bond between PDA and PVP, Jiang et al fabricated an PVP/iodine complex layer on the surface of PDA-coated PE microfiltration membrane, which grants the membrane excellent and stable anti-fouling and antibacterial properties [116].…”
Section: Post-modification By Non-covalent Conjunctionmentioning
confidence: 99%
“…Zhang et al immersed substrates into the solution containing dopamine and non-ionic polymers for co-deposition coatings [133], and found that PEG and polyvinyl alcohol (PVA) are trapped in the PDA coating without any covalent bonding, while strong hydrogen-bond acceptor like poly(N-vinyl pyrrolidone) (PVP) would suppress the assembly of PDA and decrease the deposition amount of PDA. Taking advantage of the strong hydrogen bond between PDA and PVP, Jiang et al fabricated an PVP/iodine complex layer on the surface of PDA-coated PE microfiltration membrane, which grants the membrane excellent and stable anti-fouling and antibacterial properties [116].…”
Section: Post-modification By Non-covalent Conjunctionmentioning
confidence: 99%
“…[19,20] Molecules of interest can also be co-deposited simultaneously with dopamine in a one-step reaction to create surfaces with desired properties. [2123] …”
mentioning
confidence: 99%
“…28 Polymers deposited using this method include dextran, poly(sulfobetaine methacrylate) and several nonionic polymers. [29][30][31] These depositions, however, have poor chemical stability and poor resistance to acidic solvents because the polymers are not covalently bonded to the PDA. Alternatively, a method has been developed to copolymerize dopamine with polyethyleneimine, Rupturing cancer cells by the expansion of functionalized stimuli-responsive hydrogels Y Fang et al which is an amino-rich polymer.…”
Section: Resultsmentioning
confidence: 99%